THE ROLE OF PSYCHOLOGICAL SUPPORT IN MITIGATING THE EFFECTS OF THE PUERPERAL STATE: INTERDISCIPLINARY LEGAL ANALYSIS (ESMAT Magazine, 2025)
Summary: The present study investigates the effects of the puerperal state on women's psychological health, paying attention to the impacts of a mental and emotional nature. This delicate period, marked by the transition to motherhood, was analyzed regarding the beneficial influence of psychological intervention, aiming both at coping with adversities and at preventing potential psychological illnesses, with the central objective of this study being to evaluate the role played by psychology professionals in the puerperal state, highlighting how their intervention can mitigate the adverse effects on women's mental and emotional health. Objective: Specifically, we sought to understand how psychology, with an emphasis on the psychoanalytic approach, can be used effectively to help women during the postpartum period. Methodology: The methodology adopted in this research was based on a critical literary review of contemporary works that address psychology during the puerperal state. Recent studies and specialized books that explore the various psychological aspects of this period were used as a primary source. The psychoanalytic approach was particularly chosen as a theoretical framework, due to its ability to deeply investigate the unconscious processes and emotional dynamics that permeate the puerperal state. Result: Psychoanalysis, with its emphasis on understanding psychic complexities, proved to be instrumental in identifying and resolving internal conflicts that may arise during the puerperal state. Conclusion: This study concludes the relevance of psychological intervention during the puerperal state, showing how psychology, through the psychoanalytic approach, can not only mitigate negative impacts on mental health, but also promote a more integrative and satisfactory experience of motherhood.
Keywords: Psychoanalysis; Puerperal State; Coping; Mental Health